Economic propaganda as a form of business communication - Đelošević Ivana; Spasojević Branka (Ekonomski Signali, 2025)
Economic propaganda, as a form of promotion, is a paid method of business communication that aims to transmit information, develop preference and encourage action in favor of the company's products and services. Economic propaganda as an activity consists of a series of procedures and methods through which the company establishes a communication link with potential consumers. For successful growth and development, companies must count on the long-term effects of their activities, which leads to the fact that new tasks are set before propaganda. Considering that the purpose of business communication is the promotion of products and services, image building, employee orientation, we can say that business communication is of great importance for the promotional activities of companies.